2017
DOI: 10.1002/cctc.201701301
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensionally Hierarchical Pt/C Nanocomposite with Ultra‐High Dispersion of Pt Nanoparticles as a Highly Efficient Catalyst for Chemoselective Cinnamaldehyde Hydrogenation

Abstract: A monolithic carbon‐supported Pt nanocomposite with an interconnected three‐dimensionally hierarchical porous carbon framework and ultra‐high dispersion of Pt nanoparticles (Pt/3DHPC) is synthesized by using an effective “liquid phase impregnation template” strategy. The obtained Pt/3DHPC possesses rich mesoporosity and a low amount of oxygen‐containing functional groups, which notably improve the accessible internal surface area of macropores, number of active Pt sites, and electron transfer ability. When use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 71 publications
0
16
1
Order By: Relevance
“…Catalyst stability in the liquid-phase hydrogenation was generally evaluated in a batch reactor by recycling experiments. Most of the reported catalysts showed a slightly decreased activity after five cycles. ,,, Recently, Hu et al developed three-dimensional hierarchical porous carbons (3DHPCs) for the hydrogenation of CAL, and the activity and selectivity over Pt/3DHPCs remained almost unchanged after 15 cycles. From the viewpoint of industrial applications, it remains a challenge to develop a catalyst with long-term stability for liquid-phase hydrogenation.…”
Section: Catalyst Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Catalyst stability in the liquid-phase hydrogenation was generally evaluated in a batch reactor by recycling experiments. Most of the reported catalysts showed a slightly decreased activity after five cycles. ,,, Recently, Hu et al developed three-dimensional hierarchical porous carbons (3DHPCs) for the hydrogenation of CAL, and the activity and selectivity over Pt/3DHPCs remained almost unchanged after 15 cycles. From the viewpoint of industrial applications, it remains a challenge to develop a catalyst with long-term stability for liquid-phase hydrogenation.…”
Section: Catalyst Stabilitymentioning
confidence: 99%
“…66 This was explained by the fact that the smaller curvature of the outermost tube in MWCNT4 has a smaller nonplanar degree of the rehybridized sp 2 configuration, leading to inefficient electron transfer from the carbon support to the active sites. Recently, Hu et al 119 developed a threedimensional hierarchical porous carbon framework (Pt/ 3DHPC) by a "liquid phase impregnation template" method. This carbon material was beneficial for the dispersion of Pt and exhibited a strong electron transfer ability and thereby gave a high selectivity to COL.…”
Section: Selective Hydrogenation Of Ual To Uolmentioning
confidence: 99%
“…Due to the spatial resistance of the benzene ring, the planar molecule structure of CAL cannot be adsorbed in parallel on the metal surface. It is found that only when the distance between the benzene ring and the metal surface of the catalysts is > 0.3 nm can the CAL be adsorbed on the metal surface of the catalyst . This allows the C=O double bond to have a smaller distance from the metal surface to that of the C=C double bond.…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity to cinnamyl alcohol over some carbon supported platinum‐based catalysts is not higher than 50 %, such as, for example, acetylene black (S col = 27 %), AC (S col = 30 %), mesoporous AC (S col = 33 %), expanded graphite (S col = 45 %) . Moreover, new types of carbon‐based porous materials supported platinum‐based catalysts have a higher selectivity to cinnamyl alcohol, up to 91.1 %, such as carbonized aerosols (S col = 53 %), CNTs (S col = 64 %), graphite (S col = 72 %), rice husk mesoporous carbon (S col = 88 %), graphene oxide (S col = 88 %), and three‐dimensional layered porous carbon (S col = 91.1 %) . On the other hand, platinum‐based catalysts doped with other metals, such as Fe (S col = 85 %, 90 %), Fe 3 O 4 (S col = 94.9 %), Sn (S col = 78 %), and Co (S col = 87.9 %), can also significantly improve the selectivity to cinnamyl alcohol, however, Ni (S col = 8 %, 27.4 %) is an exception.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on the modification of Pt catalyst with various metal species, but the yield of unsaturated alcohols had been far from satisfactory. Recently, reduced graphene oxide-supported SnO-isolated Pt3Sn alloy (Pt3Sn/SnO2/rGO) 88) , three-dimensionally hierarchical Pt/C nanocomposite (Pt/3DHPC) 91) and Pt3Fe zigzag nanowires (PtFe ZNWs) 92) achieved high yields of the target crotyl alcohol (75-96 %), and particularly Pt3Sn/ SnO2/rGO and Pt/3DHPC showed quite high formation rates, although high temperature and high H2 pressure were necessary. Ir-based heterogeneous catalysts were also effective for the reaction (Table 1) 75),76), 89) .…”
Section: Selective Hydrogenation Of Unsaturatedmentioning
confidence: 99%